(untitled) (Physical Education, Health and Social Sciences, 2025)
TCR-based therapies represent a groundbreaking step forward in cancer immunotherapy, leveraging the immune system’s ability to identify and kill cancer cells. This review explores the latest strategies and regulation updates influencing TCR-targeted therapies, presenting an integrated picture of their scientific rationale, recent developments, and prospective future directions. The review first describes the fundamental mechanisms of TCR-derived therapy, highlighting how TCRs recognize intracellular tumor-associated antigens presented by major histocompatibility complex (MHC) molecules. The review then discusses some of the main challenges of the field, including antigen specificity, TCR affinity, off-target toxicity, and tumor heterogeneity, which hinder the discovery of safe and effective therapies. New technologies like gene editing, synthetic biology, and high-throughput screening are revolutionizing TCR design and delivery to target more precisely and with improved safety profiles. At the same time, regulatory mechanisms are being reformatted to address the challenges of engineered T-cell therapies through revised guidelines and oversight. Clinical trials have also produced promising outcomes, especially in hematologic malignancies and a few solid tumors, demonstrating the therapeutic potential of TCR-based therapies. Results from case studies identify successes and limitations, giving useful insights to maximize treatment effectiveness. In the future, the review underlines the need to create predictive models, investigate combination treatments, and provide more widespread access to personalized immunotherapies. With ongoing advances in research and development, TCR-derived therapy has the potential to become the cornerstone of future cancer treatment—subject to scientific, clinical, and regulatory matters being resolved in harmony.